AMPLITUDE, FRESNEL ZONE, AND NMO VELOCITY FOR PP AND SS NORMAL-INCIDENCE REFLECTIONS - Iversen E. (My University, 2006)
Inspired by recent ray-theoretical developments, the theory of normal-incidence rays is generalized to accommodate P- and S-waves in layered isotropic and anisotropic media. The calculation of the three main factors contributing to the two-way amplitude - i.e., geometric spreading, phase shift from caustics, and accumulated reflection/ transmission coefficients - is formulated as a recursive process in the upward direction of the normal-incidence rays. This step-by-step approach makes it possible to implement zero-offset amplitude modeling as an efficient one-way wavefront construction process. For the purpose of upward dynamic ray tracing, the one-way eigensolution matrix is introduced, having as minors the paraxial ray-tracing matrices for the wavefronts of two hypothetical waves, referred to by Hubral as the normal-incidence point (NIP) wave and the normal wave. Dynamic ray tracing expressed in terms of the one-way eigensolution matrix has two advantages: the formulas for geometric spreading, phase shift from caustics, and Fresnel zone matrix become particularly simple, and the amplitude and Fresnel zone matrix can be calculated without explicit knowledge of the interface curvatures at the point of normal-incidence reflection. © 2006 Society of Exploration Geophysicists. All rights reserved.
Keywords: ANISOTROPIC MEDIA; SEISMIC WAVES